2022
DOI: 10.3390/metabo12050411
|View full text |Cite
|
Sign up to set email alerts
|

Renin–Angiotensin System in Liver Metabolism: Gender Differences and Role of Incretins

Abstract: The impaired hepatic lipids and carbohydrates metabolism result in various metabolic disorders, including obesity, diabetes, insulin resistance, hyperlipidemia and metabolic syndrome. The renin–angiotensin system (RAS) has been identified in the liver and it is now recognized as an important modulator of body metabolic processes. This review is intended to provide an update of the impact of the renin–angiotensin system on lipid and carbohydrate metabolism, regarding gender difference and prenatal undernutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Angiotensin II, a mediator of RAS, has emerged as a multifunctional cytokine with growth factor, pro-fibrogenic and pro-inflammatory properties. Angiotensin II also plays a role in lipid metabolism [7] . Ma et al [8] reported that angiotensin II induced lipid accumulation in human renal mesangial cells (HMCs).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II, a mediator of RAS, has emerged as a multifunctional cytokine with growth factor, pro-fibrogenic and pro-inflammatory properties. Angiotensin II also plays a role in lipid metabolism [7] . Ma et al [8] reported that angiotensin II induced lipid accumulation in human renal mesangial cells (HMCs).…”
Section: Discussionmentioning
confidence: 99%
“…The RAS plays a major role in regulating blood pressure, while emerging evidence suggested that dysregulated RAS might be associated with metabolic disorders, such as hyperglycemia ( 36 ). In particular, the hepatic RAS was implicated to affect the hepatic glucose production ( 37 ). In the RAS, the ACE/AT1 axis exerts detrimental effects, while, the ACE2/MasR axis plays a counter-balancing role ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] The ACE/AngII/AT1R axis is described as a cascade in which renin converts angiotensinogen to Ang I, which is converted to Ang II by ACE. [ 25 ] ACE2 catalyzes the conversion of Ang II to Ang 1–7, ACE2/Ang 1–7/Mas axis intrinsically induced protective actions by countering regulation ACE‐Ang II‐AT1R axis. [ 26 ] The local RAS system exists in liver tissue, independent of the circulating RAS, [ 26 ] and the local RAS was identified as an important metabolic system that plays an essential role in lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%